Rapid treatment of suicide states in the emergency department. (1st March 2011) - Larkin, G L; Beautrais, A L; Lippmann, M
Abstract : Background: Suicidal behaviour is a pervasive and pressing public health burden. Emergency Departments (EDs) visits for mood disorders in general, and for major depression, suicidal ideation, and suicide attempts in particular, have increased in the last 15 years, showing no sign of declining. Intervening with effective treatments in the ED when suicidal patients are accessible could achieve a more rapid, effective and safe disposition. At present there is a dearth of effective ED treatments for acutely suicidal and depressed patients. A single sub-anaesthetic dose of IV ketamine can rapidly reduce depressive symptoms in treatment-resistant depressed (TRD) patients, with anti-depressant responses detected within 1–2 h postinfusion and maintained in a majority of patients for 1–7 days, without significant adverse side effects. To date, research has focused on the potential of ketamine to treat TRD. Method: Pilot study to assess the feasibility of administering low-dose ketamine in the ED as a rapidly acting anti-depressant which alleviates the intensity of suicide ideation, as well as improving depressed mood. Results: 20 ED patients with a primary presenting complaint of suicide ideation or who have made a suicide attempt were administered single sub-anaesthetic dose of either ketamine (0.25 mg/kg IV bolus over 3 min). Ketamine rapidly reduced both suicide ideation and depressive symptoms. Conclusions: These results suggest the exploratory research findings of a low dose of ketamine can be translated from TRD patients to the clinical setting of the ED for suicidal patients.